2018
DOI: 10.2147/ijn.s154033
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate extract-loaded solid lipid nanoparticles: design, optimization, and in vitro cytotoxicity study

Abstract: Background Pomegranate extract (PE) is a natural product with potent antioxidant and anticancer activity because of its polyphenols content. The main purpose of this study was to maximize the PE chemotherapeutic efficacy by loading it in an optimized solid lipid nanoparticles (SLNs) formula. Materials and methods The influence of independent variables, which were lipid concentration (X 1 ), surfactant concentration (X 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 47 publications
1
42
0
1
Order By: Relevance
“…In recent years, SLNs have extensively used as a carrier for various anticancer drugs and phyto-bioactive compounds [21,27]. For example, Tamoxifen-loaded SLNs suppress breast tumors in rats [25], and pomegranate extract-loaded SLNs effectively prevent the proliferation of various cancer cells such as PC-3, MCF-7 and HepG2 [28]. The SLNs have a high drug-loading capacity, increase the blood circulation time, modulate release kinetic, increase the therapeutic efficacy of anticancer drugs, and protects the encapsulated compound from chemical degradation [29,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, SLNs have extensively used as a carrier for various anticancer drugs and phyto-bioactive compounds [21,27]. For example, Tamoxifen-loaded SLNs suppress breast tumors in rats [25], and pomegranate extract-loaded SLNs effectively prevent the proliferation of various cancer cells such as PC-3, MCF-7 and HepG2 [28]. The SLNs have a high drug-loading capacity, increase the blood circulation time, modulate release kinetic, increase the therapeutic efficacy of anticancer drugs, and protects the encapsulated compound from chemical degradation [29,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…In several studies related to the optimization of NLC production it was observed that the relative concentration of surfactant and lipids strongly affects the stability of the formulation [23]. The physical-chemical and biopharmaceutical characteristics of NLC, such as size, entrapment efficiency (EE), physical stability, drug release and morphology, are also strongly influenced by the choice and amount of lipids and surfactant [23,24,25]. Thus, an optimization of NLC production with the aid of design of experiment could be carried out with the objective of modulating the amount of liquid and solid lipids and surfactant to obtain the most desirable properties in terms particle size, entrapment efficiency and stability.…”
Section: Introductionmentioning
confidence: 99%
“…Note-se que esses efeitos podem explicar alguns achados do nosso estudo 16 . Neste, foi possível observar que o extrato da PG possui efeitos citotóxicos com efeitos inibitórios para proliferação celular nas células KB em relação às FLM durante os testes realizados 17,18 .…”
Section: Discussionunclassified